Impact of continued mailed fecal tests in the patient‐centered medical home: Year 3 of the Systems of Support to Increase Colon Cancer Screening and Follow‐Up randomized trial. Issue 2 (21st October 2015) - Green, Beverly B.; Anderson, Melissa L.; Chubak, Jessica; Fuller, Sharon; Meenan, Richard T.; Vernon, Sally W.
Abstract : BACKGROUND: The current study was conducted to determine the effect of continuing a centralized fecal occult blood test (FOBT) mailed program on screening adherence. METHODS: A patient‐level randomized controlled trial was conducted in 21 patient‐centered medical home primary care clinics between January 2010 and November 2012. A total of 2208 patients ranging in age from 52 to 75 years in a substudy of the Systems of Support to Increase Colon Cancer Screening and Follow‐Up (SOS) trial were randomized at year 3 to continued automated interventions (Continued group), which included mailed information regarding colorectal cancer (CRC) screening choices, and were mailed stool kit tests or to a group in which interventions were stopped (Stopped group). The main outcomes and measures were the completion of CRC screening in year 3 and by subgroup characteristics, respectively. RESULTS: Adherence to CRC screening in year 3 was found to be significantly higher in patients in the Continued group compared with those in the Stopped group (53.3% vs 37.3%; adjusted net difference, 15.6% [ P <.001]). This difference was entirely due to greater completion of FOBT (adjusted net difference, 18.0% [ P <.001]). Year 3 CRC screening rates were highest in patients in the Continued group completing FOBT in both years 1 and 2 (77.2%), followed by patients completing only 1 FOBT in 1 of the 2 years (44.6%), with low rates of CRC testing reported among patients not completing any FOBT within the first 2 years (18.1%). CONCLUSIONS: A centralized mailed FOBT CRC screening program continued to be more effective than patient‐centered medical home usual‐care interventions, but only for those patients who had previously completed FOBT testing. Research is needed regarding how to engage patients not completing CRC testing after being mailed at least 2 rounds of FOBT tests. Cancer 2016;122:312–321. © 2015 American Cancer Society . Abstract : This study demonstrated that a centralized mailed colorectal cancer screening program continued to be more effective than medical home clinic‐based usual care interventions.